Phase 1 study of tazemetostat in Japanese patients with relapsed or refractory B‐cell lymphoma - Munakata, Wataru (Cancer Sci, 2021)
BACKGROUND: Tazemetostat is a selective and orally available inhibitor of enhancer of zeste homolog 2 (EZH2), a histone methyltransferase and epigenetic regulator of cellular differentiation programs. We carried out a phase I study of tazemetostat in Japanese patients with relapsed or refractory B‐cell non‐Hodgkin‐type lymphoma (B‐NHL) to evaluate its tolerability, safety, pharmacokinetics, and preliminary antitumor activity. METHODS: Tazemetostat was given orally at a single dose of 800 mg on the first day and 800 mg twice daily (BID: total 1600 mg/d) on following days in a 28‐day/cycle manner. Tazemetostat dose‐limiting toxicity (DLT) was evaluated up to the end of the first treatment cycle. Archival tumor tissues were analyzed for hotspot EZH2 mutations. RESULTS: As of 15 January 2018, seven patients (four follicular lymphoma [FL] and three diffuse large B‐cell lymphoma [DLBCL]) were enrolled. The median age was 73 (range, 59‐85) years, and the median number of prior chemotherapy regimens was three (range, one to five). No DLT was observed (one patient was not evaluable due to early disease progression). The common treatment‐related adverse events (AEs) were thrombocytopenia and dysgeusia (three patients each; 42.9%). No treatment‐related serious AEs were observed. The objective response rate was 57% (4/7 patients), including responses in three of four patients with FL and one of three patients with DLBCL. An EZH2 mutation was detected in one patient with FL responding to treatment. CONCLUSIONS: Tazemetostat at 800 mg BID showed an acceptable safety profile and promising antitumor activity in Japanese patients with relapsed or refractory B‐NHL.